Ecologia reprodutiva de Lychnophora pinaster Mart. (ASTERACEAE) - Campos, Caroline Cambraia Furtado (2014)
With the greater knowledge of taxonomic genus Lychnophora issues arise regarding their reproductive biology and its possible origin and evolution, as well as its ecology and maintenance of their populations. With the aim to contribute to the elucidation, even partial, of this subject, a study was carried out on the reproductive biology and the germination process of species Lychnophora pinaster. In rocky field in municipalities of Itumirim-MG and Carrancas- MG, (two areas) we are 20 individuals between July 2012 and December 2013, registering the was clearly distinguished employing morphometric procedures floral, floral biology and floral visitors, as well as conducting experiments related to the reproductive system of the species.The experiment on the viability and germination of cipselas was conducted in the Laboratory of Forest Seeds of DCF- UFLA, Lavras, MG, being carried out x-ray tests, germination and curve of imbibition. L. pinaster presents flowers grouped in chapters three to eight flowers and these gathered in incapitulescencias approximately 13-22 chapters. Floral morphometry showed the presence of herkogamy, with differences in the heights of reproductive structures.The anthesis begins between 10:00 and 12:00 h, with few flowers opening before 10:00 a.m. and after 13:00, and the flowers have protandry. Flowering occurred in two periods of the year, being one in the month of July, with few flowers and the second from September to November, with a flowering and more intense. All treatments applied in the experiments of pollination resulted in large number of achenes without seed.The species proved to be xenógama optional, forming fruits with seeds by cross-pollination, pollination and by agamospermy, not occurring significant differences between the three areas analyzed. I registered the visit of 20 species of insects belonging to six orders. The bees Bombus morio and Xylocopa frontalis (Apidae), are effective pollinators. The chapters of L. pinaster, if showed target of hervivoria. The test of radius x, due to the large amount of empty cipselas was necessary the use of blower and after this was obtained an average of 42% of full seeds (with embryo formed). The germination test it was observed that the area Morro Janela (A1) had the highest values in relation to the number of germinated seeds differed statistically from other areas; similar values were found when analyzing the formation of seedlings being that A1 also had the highest number. The curves of imbibition showed a phase I with an average duration of 3 hours; in Morro Janela area note the change from phase II to III from 272 hours of imbibition; in the areas of Carrancas seeds reached the stage II 322 and 346 hours.